Gallbladder Fossa Abscess Rare Complication Laparoscopic Cholecystectomy: A Case Report - Mohamed, Abbas; Almotlaq, Abdulaziz M.; Alshamari, Abdulla E.; Albuqaisi, Amal A (British Journal of Healthcare and Medical Research, 2025)
Gallbladder fossa abscesses are a rare serious complication of laparoscopic cholecystectomy. We present a 62-year-old male patient who had undergone laparoscopic cholecystectomy and subsequently developed a gallbladder fossa abscess. The diagnosis was confirmed by ultrasound and computed tomography (CT), and it was successfully treated with percutaneous catheter drainage and antimicrobial therapy.